PENGARUH LAMA BLANCHING DAN TINGKAT KEMATANGAN DAUN TERHADAP AKTIVITAS ANTIOKSIDAN DAN KARAKTERISTIK ORGANOLEPTIK TEH CELUP DAUN SEMBUNG (Blumea balsamifera) - Sukmawati Uday; Zainudin Antuli; Suryani Une (Universitas Negeri Gorontalo, 2022)
Sambong leaf contains various active compounds such as essential oils, cineol, limonene, palmitin and myristin acids, tannins, glycosides, saponins, and flavonoids. Sambong leaf can be used as a basic ingredient for making herbal teas. Sambong leaf has a strong and distinctive odor and bitter taste. It is due to the saponin compounds contained in Sambong leaf. This research aimed to determine the effect of blanching time and leaf maturity level on antioxidant activity, tannin, total phenol, and organoleptic of herbal tea made from Sambong leaf using a factorial Completely Randomized Design with two factors. Factor A was the blanching time consisting of treatment levels, namely 0 minute, 3 minutes, S minutes. and 7 minutes at 60°C. Factor B was the leaf maturity level, consisting of 3 treatment levels: young, intermediate, and old Sambong leaf, with each sample weighing 200 g. ment combinations These two types of factors resulted in 12 treatment to obtain 36 experiments. Data were analyzed using the Analysis of Variance repeated three times (ANOVA) with a 0,05 confidence level and advanced Duncan's Multiple Range Test (DMRT) to determine the difference between treatments using the SPSS application. Observation parameters included analysis of total phenol, tannin, antioxidant activity, and organoleptic, Antioxidant activity was described as ICso 56.7 ppm, with total phenol of 219.4 mg GAE/g, tannin analysis in all treatments containing tannins, and the most preferred organoleptic result was the 7-minute blanching treatment with old leaf.